Influence of Water Expulsion on Structural Properties of V2O5 nH2O Sol-Gel Films - Gokdemir, F. Pinar; Menda, U. Deneb; Kavak, Pelin; Saatci, A. Evrim; Ozdemir, Orhan; Kutlu, Kubilay (AMER INST PHYSICS, 2012)
Vanadium pentoxide (V2O5) thin films were prepared by dip-coating sol-gel technique by dissolving V2O5 powder in hydrogen peroxide (H2O2), the solution, leading V2O5 sol-gel nanocrystalline films. The films under preparation were exposed different hydration states, n, varying from 6 to 2 determined via XRD measurements. Water molecules were adsorbed in layered structure of V2O5 oxide films and hence the adsorption could be described as an intercalation in which the molecules were trapped in some cavities and were not randomly oriented. (00l) pattern of X-ray diffraction analysis not only approved the one dimensional stacking of V2O5 ribbons but also served to determine basal distance from which hydration state was guessed. The basal distance were calculated from the position of 00l peak and varied from 17.2 angstrom to 10.6 angstrom that corresponded to n= 6 to n= 2 respectively. During the water departure upon heating, the basal distance reduced by steps of 2.8 angstrom (diameter of vander Walls water molecule) towards 8.8 angstrom value, attributed to n= 0.5. Contrary to common belief of three-step mass loss (two of them were ascribed water expulsion), the process took place in two steps in thermogravimetric and differential thermal analysis (TG/DTA) measurements. During the first step, decrease in d exhibited huge endothermic negative thermal expansion of V2O5 nH(2)O sol while crystallization into orthorhombic V2O5 occurred at 357 degrees C (exhothermic peak) in TG as last step.
Keywords: vanadium pentoxide; two stage mass loss; negative thermal expansion; VANADIUM; Materials Science; Physics